Biophysical and chemical stability of surfactant/budesonide and the pulmonary distribution following intra-tracheal administration - Chung-Ming Chen; Chien-Hsiang Chang; Chih-Hua Chao; Mei-Hui Wang; Tsu-Fu Yeh (Drug Delivery, 2019)
Intra-tracheal instillation of budesonide using surfactant as a vehicle significantly decreased the incidence of bronchopulmonary dysplasia or death in preterm infants. The formularity of surfactant supplemented with budesonide and biophysical and chemical stability of the suspension has not been well reported. The aims are to investigate the biophysical and chemical stability of two surfactant preparations, Survanta and Curosurf, supplemented with budesonide. Biophysical property of the surface tension of Survanta and Survanta/budesonide suspension and of Curosurf and Curosurf/budesonide suspension was conducted by a pulsating bubble surfactometer and by a drop shape tensiometer. Chemical stability of Survanta/budesonide and of Curosurf/budesonide suspensions was tested by high-performance liquid chromatography analysis (HPLC). Pulmonary distribution of Survanta/18F-budesonide suspension was examined by a Nano/PET digital scan in rats. The Marangoni effect of Survanta, Curosurf, and budesonide was tested by digital high speed photography. For Survanta supplemented with budesonide, with a concentration ratio of ≥50, the surface tension-lowering activity was minimally affected. Similarly, the surface tension-lowering activity of Curosurf was not significantly affected by addition of budesonide, if the concentration ratio was ≥160. With these concentration ratios of both suspensions, HPLC analysis revealed no new compounds identified. Curosurf as compared to Survanta exhibited a significantly higher Marangoni effect. We conclude that with current dosage recommended for Survanta and Curosurf, both surfactant/budesonide suspensions are biophysically and chemically stable. Both surfactants can act as an effective vehicle for budesonide delivery.